2015
DOI: 10.1177/1527002515609663
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous Ability and Risk Taking in a Rank-Order Tournament

Abstract: Since 2011, the National Association for Stock Car Auto Racing (NASCAR) has forced drivers to pick one of three national series for which they would be eligible to compete for a season championship. Prior to this “Pick-A-Series” rule, many drivers in the premier Sprint Cup Series competed regularly in the Nationwide Series, which is a developmental division for less experienced drivers. I examined whether the removal of moonlighting Sprint Cup drivers from championship contention encouraged less aggressive dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Beginning in 2011, NASCAR required drivers to compete in only one series in any season. Yaskewich (2017) showed that this rule change substantially changed driver behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Beginning in 2011, NASCAR required drivers to compete in only one series in any season. Yaskewich (2017) showed that this rule change substantially changed driver behavior.…”
Section: Introductionmentioning
confidence: 99%